Contracting school meals in a rural Florida district. Issue 2 (2nd December 2019) - Traynor, Mark; Chen, Can; Kitterlin, Miranda
Abstract : Purpose: The purpose of this paper is to examine the decision to contract school meal services and the associated nutritional and financial impacts on school districts. Given the increase in the use of competitive contracting of public school meal services and the critical role that school meal services play in public health, this is an important subject to investigate. Design/methodology/approach: A case study was performed using one US school district with privatized food service. Face-to-face interviews were conducted with school food service decision makers. Other data collection included the analysis of public documents such as the school district's budgets and financial statement reports (the cost per lunch and breakfast meals, the cost for labor, contract, transport, supplies and food expenses) and school food service policies (contract policies). Supplementary data pertaining to district social-demographic profiles and full-time equivalent enrollment figures were also collected from state departments. Findings: Analysis of interviews revealed that positive financial motivations and impacts were dominant factors related to contracting food services in the district. A significant finding was the relatively short turnaround in the district's negative financial situation as a result of contracting out the food services. These findings provide valuable insight and support for rural school districts in similar negative financial situations seeking to contract out food services. Originality/value: Many studies have examined contracting out of technical services, such as transport and waste management, and social services, such as correctional services and health; however, there is a lack of studies documenting the effects of contracting out of school meal services.